Pelatihan Pencegahan Kekerasan Seksual Bagi Siswa di Lingkungan Sekolah - Reni Alfiyah; Jusnawati Jusnawati; Alwi Usra Usman; A. Hardiyanti; Puji Novita Sari (Paramacitra Jurnal Pengabdian Masyarakat, 2026)
The dynamics of educational institutions, which are increasingly vulnerable to sexual violence, demand a new paradigm through strengthening students' capacities via preventive actions based on education. One way to reduce the risk of sexual violence against children in school environments is through a more participatory and context-appropriate prevention education model. This article describes the implementation of a community service program in the form of sexual violence prevention training for students in the school environment, namely at UPT SPF SMP Negeri 26 Makassar. The program is designed to strengthen students' self-protection literacy through a participatory approach that integrates dialogical lectures, group discussions, and written reflections. The novelty of the program lies in its emphasis on fostering student agency in recognizing power relations, identifying risky situations, and formulating self-protection strategies relevant to students' daily contexts at school. The results show changes in awareness and sensitivity of students' collective commitment in maintaining school safety from acts of violence. Instilling understanding of sexual risks becomes more effective when students formulate self-protection strategies. Cross-sector collaboration and participatory interaction based on dialogue for students provide solutions in addressing sensitive issues in secondary education. The main recommendation is directed towards forming a preventive synergy between the school and families to create comprehensive protection strategies.